Fifty shades darker ebook - James, E L. (Fifty Shades, 2012)
"I rest my head against him, and he kisses my hair repeatedly. This is home. He smells of linen, fabric softener, bodywash, and my favorite smell—Christian. For a moment, I allow myself the illusion that all will be well, and it soothes my ravaged soul." Daunted by the singular tastes and dark secrets of the beautiful, tormented young entrepreneur Christian Grey, Anastasia Steele has broken off their relationship to start a new career with a Seattle publishing house. But desire for Christian still dominates her every waking thought, and when he proposes a new arrangement, Anastasia cannot resist. They rekindle their searing sensual affair, and Anastasia learns more about the harrowing past of her damaged, driven and demanding Fifty Shades. While Christian wrestles with his inner demons, Anastasia must confront the anger and envy of the women who came before her, and make the most important decision of her life. Discover the world of Fifty Shades of Grey: An Instant #1 New York Times Bestseller More than 165 Million Copies Sold Worldwide One of 100 Great Reads in the Great American Read 133 Weeks on the New York Times Bestseller List This book is intended for mature audiences.